Comparison of Mehlich-3 and Ammonium Acetate Extractable Calcium and Magnesium in Kansas Soils - E. B. Rutter; D. A. Ruiz Diaz; L. Hargrave (Kansas Agricultural Experiment Station Research Reports, 2021)
The use of the Mehlich-3 (M3) soil test procedure to assess the plant availability of numerous macro and micronutrients has become common at soil testing labs across the US. Mehlich-3 is used for soil tests for phosphorus (P) and potassium (K) in Kansas; however, data for other base cations for existing methods are scarce for Kansas soils. The objective of this study was to investigate the relationship between M3 and ammonium acetate (AA) extractable calcium (Ca) and magnesium (Mg). Regression analyses indicate a near 1:1 linear relationship between M3-Mg and AA-Mg across a wide range of soil pH and soil organic matter (SOM) contents. The relationship between M3-Ca and AA-Ca was relatively constant for acidic to neutral pH soils. However, M3 extracted substantially more Ca in higher pH soils. Regression analysis indicates that M3-Ca and AA-Ca diverge exponentially at a soil pH of 7.3 and higher. Given the current interpretation of AA-Ca as a measure of exchangeable Ca, these results suggest that M3 may extract Ca from non-exchangeable soil-Ca pools in soils with above neutral pH levels. Based on these results, M3 should not be used to assess the plant availability of soil-Ca or estimate cation exchange capacity (CEC) in soils with a pH above 7.3, as the values are likely to be overestimated.
Keywords: calcium; magnesium; Mehlich-3; ammonium acetate; soil test